2017
DOI: 10.1016/j.ijcard.2017.02.142
|View full text |Cite
|
Sign up to set email alerts
|

Isolated diastolic hypertension and incident heart failure in community-dwelling older adults: Insights from the Cardiovascular Health Study

Abstract: Among community-dwelling older adults, isolated diastolic hypertension is rare and is associated with higher risk for incident HF and cardiovascular mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
(24 reference statements)
0
19
0
1
Order By: Relevance
“…We have demonstrated that isolated diastolic hypertension, defined as DBP ≥90 mm Hg and SBP <140 mm Hg, a rare form of hypertension in older adults, may be associated with a higher risk of incident HF. 12 In contrast, a low DBP has been shown to be a risk factor for incident HF in this population. 8 In a propensity-matched cohort of CHS participants in which those with and without isolated diastolic hypotension (DBP <60 mm Hg) were balanced on 58 baseline characteristics including a mean SBP of 130 and 131 mm Hg (among those with and without diastolic hypotension, respectively), DBP <60 mm Hg was independently associated with a significant 33% higher risk of developing new-onset HF.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have demonstrated that isolated diastolic hypertension, defined as DBP ≥90 mm Hg and SBP <140 mm Hg, a rare form of hypertension in older adults, may be associated with a higher risk of incident HF. 12 In contrast, a low DBP has been shown to be a risk factor for incident HF in this population. 8 In a propensity-matched cohort of CHS participants in which those with and without isolated diastolic hypotension (DBP <60 mm Hg) were balanced on 58 baseline characteristics including a mean SBP of 130 and 131 mm Hg (among those with and without diastolic hypotension, respectively), DBP <60 mm Hg was independently associated with a significant 33% higher risk of developing new-onset HF.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, patients in the SDH group in our study represent those with true SDH as opposed to being diluted by those with misclassified ISH. Thus, both higher SBP and DBP may have contributed to the higher risk of HF in the SDH group, 12 and a low to low-normal DBP may have been accentuated the risk of HF in the ISH group. 8 It is possible that without the confounding association of low DBP with incident HF in ISH, the true risk of HF in ISH would be lower than that in SDH.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been recognized that after 50 years old, the systolic BP continuously increases with age, while on the other hand, the diastolic BP starts to decrease with age. Therefore, IDH is more prevalent in young and middle-aged patients, but ISH is more prevalent in middle-aged and old patients [8,17]. Thus, the management of IDH should be highlighted rather than ignored in younger patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Besides antihypertensive medication, lifestyle management also plays a fundamental role in the management of hypertension concerning the high nonadherence rate in young patients [8][9][10]. But life style management may have a different effect on different types of hypertension like IDH and ISH, which are considered to have different pathophysiological mechanisms and will result in various features [11].…”
Section: Trial Registrationmentioning
confidence: 99%
“…It is obvious that the described studies present only in the limited form the most important issues from the area of blood pressure, including the above-mentioned, just being published, new ACC/AHA 2017 guidelines [37], which will be reviewed and presented in details separately. Thus, it is worth to mention at least about the other important studies, including the ones on the role of antihypertensive therapy on arterial stiffness [38], on the role of fixed combination/polypill therapy on complicated hypertension in patients with many other risk factors [39][40][41][42][43][44][45][46][47], as well as on the relation on relation of supine BP to sitting BP and ambulatory BP with regard to identification of diagnostic cut-offs for hypertension [48].…”
Section: Blood Pressure Update 2016mentioning
confidence: 99%